A Novel Three-Input Field Effect Transistor with Parallel Switching Function Using T-Shaped Channel. (11th April 2022) - Mo, Zening; Jiang, Zhidi; Hu, Jianping
Abstract : In this article, a novel three-input field effect transistor with parallel switching function (PSF-TiFET) is proposed. The channels of the new device consist of a vertical subchannel and two horizontal subchannels. The two horizontal subchannels are manufactured over the vertical subchannel by using smart-cut process. The top gate is located above the two horizontal subchannels. The front gate and back gate below the two horizontal subchannels are located on the two sides of the vertical subchannel, respectively. Each of the all three gates has roughly the same control area on the channel, and thus, the all three gates have roughly the same effect on the device channel. Due to its special structure, the new device is logically equivalent to three conventional single-input transistors in parallel. Compared with the traditional field effect transistors with a single-input terminal, the new device can be used to simplify the circuit with the reduced transistor number. The impacts of body thickness, gate oxide thickness, and work function on device performance are investigated, and then the device optimizations are carried out. The current characteristic of the device is theoretically analyzed. Silvaco TCAD simulations show that the theoretical analysis agrees well with the TCAD simulation results. This work explores the feasibility of multi-input devices, which would facilitate its development.